Anytime, anywhere access to information resources: a case study from Kuwait. Issue 7 (20th September 2019) - Buarki, Hanadi Jumah; Dar, Saleeq Ahmad
Abstract : Purpose: The purpose of this paper is to understand the pervasiveness of mobile devices in ubiquitous access of information. Moreover, the study tries to ascertain the growing demands of mobile devices in library settings. Design/methodology/approach: A survey was administered to gain in-depth information regarding the use of mobile devices and their use in information access. Further, it investigated the general uses of mobile devices in day to day life. The survey also contained some questions aimed at obtaining more comprehensive information about the impediments faced by the students in library settings and the way out. Findings: The study highlights the rapid growth of mobile device usage among students at the College of Basic Education, Public authority for Applied Education and Training, Kuwait, and indicates the urgent need of libraries to the embrace mobile web. Originality/value: The use of mobile devices in comfort zones demands libraries to disseminate information anytime, anywhere. This study examines the academic library users' insistence for such services and the competence of libraries to provide services "on the go".